Various Adjuvants Effect on Immunogenicity of Puumala Virus Vaccine - Kurashova, Svetlana S.; Ishmukhametov, Aidar A.; Dzagurova, Tamara K.; Egorova, Maria S.; Balovneva, Maria V.; Nikitin, Nikolai A.; Evtushenko, Ekaterina A.; Karpova, Olga V.; Markina, Anna A.; Aparin, Peter G.; Tkachenko, Petr E.; L`vov, Vyatcheslav L.; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Various adjuvants effect on the immunogenicity of the candidate inactivated Puumala virus vaccine was detected in BALB/c mice. Adjuvants under study were: aluminum hydroxide, spherical particles of Tobacco mosaic virus envelope protein, B subunit of heat-labile enterotoxin of Escherichia coli, and low endotoxic lipopolysaccharide of Shigella sonnei. Aluminum hydroxide (1 mg/ml) did not affect neutralizing antibodies induction and vaccine stability during storage compared to immunization with the vaccine without adjuvant. B subunit of heat-labile enterotoxin (0.2 µg/ml), low endotoxic lipopolysaccharide (50 µg/ml), and spherical particles (300 µg/ml) significantly enhance the humoral immune response of vaccine (p < 0.0001). Pronounced stimulation of IL-12 and INF-ɣ as indicators of T-cell immunity activation was observed when mice were immunized with vaccines either with or without adjuvants. It has been shown that low endotoxic lipopolysaccharide contribute not only to enhance the immune response but also to stabilize Puumala virus vaccine during storage.